2021
DOI: 10.1007/s13246-021-01060-9
|View full text |Cite
|
Sign up to set email alerts
|

AI-based diagnosis of COVID-19 patients using X-ray scans with stochastic ensemble of CNNs

Abstract: According to the World Health Organization (WHO), novel coronavirus (COVID-19) is an infectious disease and has a significant social and economic impact. The main challenge in fighting against this disease is its scale. Due to the outbreak, medical facilities are under pressure due to case numbers. A quick diagnosis system is required to address these challenges. To this end, a stochastic deep learning model is proposed. The main idea is to constrain the deep-representations over a Gaussian prior to reinforce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Such challenges can be addressed with robustly trained AI models and selection of appropriate cut-off values that maintain a good balance of sensitivity and specificity across different radiography units and radiographic quality. Although we did not compare the performance with other models in the literature, the AUCs from of our AI algorithm was similar to those reported for other models assessed with open access CXR datasets (https://nihcc.app.box.com/v/ChestXray-NIHCC/file/220660789610) (20). Apart from detection of radiographic findings assessed in our study with an AI algorithm, other studies have also assessed applications of AI for prioritizing interpretation of CXRs to expedite reporting of abnormal CXRs and specific findings (21).…”
Section: Discussionsupporting
confidence: 53%
“…Such challenges can be addressed with robustly trained AI models and selection of appropriate cut-off values that maintain a good balance of sensitivity and specificity across different radiography units and radiographic quality. Although we did not compare the performance with other models in the literature, the AUCs from of our AI algorithm was similar to those reported for other models assessed with open access CXR datasets (https://nihcc.app.box.com/v/ChestXray-NIHCC/file/220660789610) (20). Apart from detection of radiographic findings assessed in our study with an AI algorithm, other studies have also assessed applications of AI for prioritizing interpretation of CXRs to expedite reporting of abnormal CXRs and specific findings (21).…”
Section: Discussionsupporting
confidence: 53%
“…Similarly, Makris A. et al [43,44] used five different pre-trained CNN models and achieved 95% accuracy. Arora, R. et al [45] proposed stochastic deep learning model using ensemble of slandered convolutional models and evaluate developed model on standard dataset contain three classes: COVID-19, normal and pneumonia and attain an accuracy and AUC of 0.91 and 0.97, respectively. A detailed comparison is illustrated in Figure 6 and Table 6.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not compare the AI’s performance with other models from the literature, the AUCs of our AI algorithm were similar to those reported for other models assessed using open access CXR datasets ( (accessed on 4 August 2022)) [ 25 ]. Apart from detection of radiographic findings assessed in our study with an AI algorithm, other studies have assessed applications of AI for prioritizing interpretation of CXRs in order to expedite reporting of abnormal CXRs and specific findings [ 26 ]. Baltruschat et al reported the use of AI-based worklist prioritization for a substantial reduction in reporting turnaround time for critical CXR findings [ 27 ].…”
Section: Discussionmentioning
confidence: 99%